2006
DOI: 10.1196/annals.1364.049
|View full text |Cite
|
Sign up to set email alerts
|

Women and Reproductive‐Related Trauma

Abstract: Women are at higher risk for developing posttraumatic stress disorder (PTSD) than men, leading to significant psychosocial burden and healthcare-related costs. Research has shown an association between the negative impact of traumatic experiences and the reproductive life cycle in women. Pregnant women with a history of abuse/trauma frequently report intrusive reemergence of symptoms. Women who experience miscarriage may present with even higher prevalence rates of PTSD symptoms. Both psychologic and physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
6
0
4
Order By: Relevance
“…The highest level of distress measured in this study was experienced by women who self-identified as "infertile" [111]. A similar survey of couples attending a fertility clinic found 41% of women had depression and 87% had anxiety [112] and a review suggests that pregnant women who have experienced miscarriage previously may experience even higher rates of stress disorder symptoms [113]. In a population-level study of the impacts of large-scale social and economic upheavals in China 1955-1987 on miscarriage and stillbirth prevalence, an overall pattern of two peaks corresponding with the Cultural Revolution and Great Leap Forward were identified by Cai and Feng [114].…”
Section: Inhibition Of Th1 Cytokines In Lymphocytesmentioning
confidence: 82%
“…The highest level of distress measured in this study was experienced by women who self-identified as "infertile" [111]. A similar survey of couples attending a fertility clinic found 41% of women had depression and 87% had anxiety [112] and a review suggests that pregnant women who have experienced miscarriage previously may experience even higher rates of stress disorder symptoms [113]. In a population-level study of the impacts of large-scale social and economic upheavals in China 1955-1987 on miscarriage and stillbirth prevalence, an overall pattern of two peaks corresponding with the Cultural Revolution and Great Leap Forward were identified by Cai and Feng [114].…”
Section: Inhibition Of Th1 Cytokines In Lymphocytesmentioning
confidence: 82%
“…Même en l'absence de facteurs de vulnérabilité établis, tous les accidents obsté-tricaux sévères (avortement spontané, interruption tardive de grossesse, naissance d'un enfant mort-né, état hémorra-gique sévère, etc.) sont susceptibles de conduire à un état de stress [110]. Des incidents mineurs de la procédure obstétricale (travail douloureux prolongé, indication de césa-rienne, etc.)…”
Section: Troubles Caractérisésunclassified
“…There is a growing body of research in PTSD related to childbirth and perinatal complications (Alcorn et al 2010; Ayers et al 2009; Forray et al 2009; Maggioni et al 2006), recognizing that prior reproductive trauma may increase a woman’s risk for the re-emergence of PTSD symptoms and other mental health problems during the perinatal period (Born et al 2006). However, it is also known that many women experience traumatic events well before their childbearing years and may enter pregnancy with mental health problems, including PTSD (Goebert et al 2007; Mezey et al 2005; Morland et al 2007; Rodríguez et al 2010; Yampolsky et al 2010), which may be undiagnosed or untreated.…”
Section: Introductionmentioning
confidence: 99%